The role of AIM2 in inflammation and tumors - Yu, Dalang; Zheng, Siping; Sui, Lina; Xi, Yuling (Frontiers in Immunology, 2024)
Absent in melanoma 2 (AIM2) serves as an intracellular nucleic acid sensor that predominantly detects double-stranded DNA (dsDNA) within the cells. This detection initiates the assembly of inflammasome and activates the inflammasome signaling cascade, resulting in the production of inflammatory mediators and the cleavage of Gasdermins. Consequently, these processes culminate in inflammatory responses and pyroptotic cell death. AIM2 plays a pivotal role in modulating inflammation and tumorigenesis, functioning through both inflammasome-dependent and independent mechanisms. Its influence on the host immune response is dual-faceted, exhibiting both promotive and inhibitory effects in the contexts of inflammation and tumors. These effects are predominantly contingent upon the specific cell type expressing AIM2 and the nature of the host’s disease. This article seeks to review the latest advancements in understanding the cell-specific functions of AIM2 in inflammation and tumorigenesis, with the objective of offering insights for further research on AIM2 and informing the development of targeted therapeutic strategies for clinical application.